2017
DOI: 10.1021/acsami.6b16250
|View full text |Cite
|
Sign up to set email alerts
|

Urea-Assisted Room Temperature Stabilized Metastable β-NiMoO4: Experimental and Theoretical Insights into its Unique Bifunctional Activity toward Oxygen Evolution and Supercapacitor

Abstract: Room-temperature stabilization of metastable β-NiMoO is achieved through urea-assisted hydrothermal synthesis technique. Structural and morphological studies provided significant insights for the metastable phase. Furthermore, detailed electrochemical investigations showcased its activity toward energy storage and conversion, yielding intriguing results. Comparison with the stable polymorph, α-NiMoO, has also been borne out to support the enhanced electrochemical activities of the as-obtained β-NiMoO. A specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(78 citation statements)
references
References 65 publications
2
76
0
Order By: Relevance
“…(c) Schematic illustration of the exposed crystal planes and (d) LSV curves of the NiCo 2 O 4 nanosheet, NiCo 2 O 4 octahedron, NiCo 2 O 4 truncated octahedron . (e) Polarization curves for α‐NiMoO 4 and β‐NiMoO 4 , and IrO 2 /C in 1 m KOH solution . (f) Schematic illustration of atomically thin NiFe 2 O 4 quantum dots (AT NiFe 2 O 4 QDs) for OER electrocatalysis …”
Section: Other Ni‐based Oxidesmentioning
confidence: 99%
See 3 more Smart Citations
“…(c) Schematic illustration of the exposed crystal planes and (d) LSV curves of the NiCo 2 O 4 nanosheet, NiCo 2 O 4 octahedron, NiCo 2 O 4 truncated octahedron . (e) Polarization curves for α‐NiMoO 4 and β‐NiMoO 4 , and IrO 2 /C in 1 m KOH solution . (f) Schematic illustration of atomically thin NiFe 2 O 4 quantum dots (AT NiFe 2 O 4 QDs) for OER electrocatalysis …”
Section: Other Ni‐based Oxidesmentioning
confidence: 99%
“…They discovered that 0.61NiMnO 3 /NiMn 2 O 4 delivered optimal overall bifunctional activity since the surface Ni 3+ favors OER activity while the surface Mn 3+ with a small amount of Mn 4+ facilitates ORR processes. Rout's group demonstrated that metastable β‐NiMoO 4 was more active for OER than α‐NiMoO 4 (Figure e) . Ma's group fabricated atomically thin NiFe 2 O 4 quantum dots with different lateral sizes as an efficient OER catalyst through a mild and controllable method (Figure f) …”
Section: Other Ni‐based Oxidesmentioning
confidence: 99%
See 2 more Smart Citations
“…At atmospheric pressure, there are two phases of NiMoO 4 both with a monoclinic structure: α‐NiMoO 4 (low‐temperature stable phase) and β‐NiMoO 4 (high‐temperature stable phase). The most striking difference between those two polymorphs is the coordination of the Mo 6+ ions, with pseudo‐octahedral coordination in the α‐NiMoO 4 phase and distorted tetrahedral coordination in the β‐NiMoO 4 phase . Generally, β‐NiMoO 4 has a higher intrinsic conductivity and reactivity than α‐NiMoO 4 , but it is very difficult to prepare and maintain.…”
Section: Introductionmentioning
confidence: 99%